Customer Relationship Management (CRM) and Logistic Customer Satisfaction - Wareewanich, Thitinant; Sukpasjaroen, Khunanan; Chankoson, Thitinan; Ruaengmaneeya, Nattapat; Raviyan, Nipont (International Journal of Supply Chain Management, 2019)
Worldwide logistic industry is growing rapidly. Due to the extensive volume of logistics, companies overlooked the important challenge of customer satisfaction which effect adversely to performance of these companies. Low customer satisfaction level is now challenge for logistic companies, particularly in Indonesia. That is the reason the logistic performance is low among Indonesian logistic companies. According to the estimations, Indonesian logistics has low ranking as compared to various emerging economics such as Thailand, Malaysia, India, Chile, Brazil etc. It is found that the companies have low level of customer relationship management (CRM). Thus, this study attempted to address the crucial issues in Indonesian logistic industry and focused on customer relationship management (CRM) to increase the satisfaction level of logistic customers. In this study, customer orientation and technology-based CRM activities are considered to examine the effect on customer satisfaction. Knowledge management is taken as moderating variable. It is found that customer relationship management (CRM) has significant positive effect on customer satisfaction. Knowledge management strengthens the positive relationship between customer relationship management (CRM) practices and logistic customer satisfaction.